Phenobarbital induction of drug/steroid-metabolizing enzymes and nuclear receptor CAR - Kakizaki, Satoru; Yamamoto, Yukio; Ueda, Akiko; Moore, Rick; Sueyoshi, Tatsuya; Negishi, Masahiko (BBA - General Subjects, 2003)
Phenobarbital (PB) increases hepatic drug/steroid-metabolic capability by coordinately activating transcription of the genes encoding various metabolizing enzymes. The nuclear receptor CAR was first implicated as a transcription factor that activates the cytochrome P450 Cyp2b10 gene. In response to PB, CAR forms a heterodimer with the retinoid X receptor (RXR), binds to a PB response element (typified by DR-4 motif), and activates transcription of the gene. In the CAR-null mouse, PB does not only induce the Cyp2b10 gene, but also induces genes encoding various metabolizing enzymes. Thus, CAR is a general nuclear receptor that is essential for PB induction of drug/steroid metabolizing enzymes. PB also induces amino levulinate synthase 1 (ALAS-1), the rate-limiting enzyme in heme biosynthesis, to increase heme supply. However, PB induction of the synthase occurs in CAR-null mice, suggesting that CAR does not coordinate the heme synthesis for the induction of drug/steroid metabolism.